Lemon juice antioxidant activity against oxidative stress (Baghdad Science Journal, 2020)
This study is conducted to evaluate the therapeutic and antioxidant effect of lemon juice on some hematological and biochemical parameters. Thirty female mice used in this study were exposed to oxidative stress through giving them hydrogen peroxide in drinking water for 30 days. Animals randomly distributed over 3 groups, each group contained 10 animals and treated as follows: T1 control group (drinking distilled water only), T2 (0.75% hydrogen peroxide in drinking water) and T3 (0.75% hydrogen peroxide in drinking water with daily drenching with 1 mL lemon juice). At the end of the experiment, blood samples were collected from animals for evaluating the following hematological and biochemical parameters: Haemoglobin concentration (Hb), red blood cells count (RBC), white blood cells count (WBC), packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), platelet count (PLT), level of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and total protein. The results showed that T3 exhibited an enhancement in RBC count, Hb concentration, WBC, lymphocyte and total protein and reduction in the level of AST and ALT compared to T2. These findings clearly revealed the advance protective and antioxidant features of lemon juice on hematological and biochemical parameters of the oxidatively stressed female mice.